Design and Development of IoT-Enabled Portable Device for Multiparameter Air Quality Monitoring - DERBY BRYLIAN ADINARA; AGUSTINA RACHMAWARDANI; ADI WIDIATMOKO WASTUMIRAD; BENYAMIN HERYANTO RUSANTO; DWI INDRA PRASETYO; HANIF KURNIAWAN; ABDUL MANAF HANI (Institut Teknologi Nasional, Bandung, 2025)
The limitations of Indonesia's air quality monitoring infrastructure have prompted research to develop portable Internet of Things (IoT)-based monitoring devices. The system is designed using ESP32 and Arduino Uno integrated with MQ136 (SO2), MQ131 (NO2), MiCS-5524 (CO), TGS-2611 (CH4), Gravity-0460 (PM), and Gravity-0321 (O3) sensors. Data is converted into AQI values and displayed via LCD, Telegram, and website. The device is equipped with an early warning system that includes a buzzer, a website pop-up, and Telegram messages. Field testing results over 24 hours at POS KU Cibeureum recorded peak concentrations of PM2.5 (19 μg/m³), PM10 (58 μg/m³), NO₂ (1.375 ppb), CO (238 ppb), SO₂ (0.74 ppb), and O₃ (45 ppb). The device can be operated portably with the following dimensions: enclosure I, 20×20 cm; enclosure II, 7×12 cm; control panel box, 30×40 cm (pre-assembled) and 100×180 cm (post-assembled). The device has proven effective as an adaptive monitoring solution for residential areas surrounding industrial zones.